2015
DOI: 10.1007/s10661-014-4233-4
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of bioindicator selection for ecological, human, and cultural health: Chinook salmon and red knot as case studies

Abstract: There is considerable interest in developing bioindicators of ecological health that are also useful indicators for human health. Yet, human health assessment usually encompasses physical/chemical exposures and not cultural well-being. In this paper, we propose that bioindicators can be selected for all three purposes. We use Chinook or king salmon (Oncorhynchus tshawytscha) and red knot (Calidris canutus rufa, a sandpiper) as examples of indicators that can be used to assess human, ecological, and cultural he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The tangible outcome of the project, which required over 5 years to complete, was a report to DOE laying out our findings (Burger et al., 2015; CRESP, 2015; Gochfeld & Burger, 2014). The main findings were that: (1) salmon life cycles are varied and complex (involving spring and fall runs, Healey, 1991), (2) having good population estimates by species and runs is critical (Hyun et al., 2012a,b), (3) several species of salmon spend a significant part of their life cycle in the Columbia River (and mainly in the Hanford Reach) where they spawn (Hayes et al., 2013), (4) contaminants are not viewed generally by the State or DOE as a significant stressor on salmon, especially compared to other stressors (CRESP, 2015; NRC, 1996; Regetz, 2003; Tiller et al., 2004), (5) laboratory experiments indicated that there is a great deal of variability in results, no effects were found at Hanford‐relevant chromium exposures on fertilization, hatching, and exposure of alevins (early stage on salmon), but there were some laboratory effects of chromium on later stages of fry (Farag et al., 2006a,b; Patton et al., 2007), and (6) at some periods of time the fry may be vulnerable to chromium if they remain near the gravel surface where the pore water and river water meet (Burger et al., 2015; CRESP, 2015; Gochfeld & Burger, 2014). The Tribes, however, remained concerned about potential long‐term effects of contaminants on eggs and fry of salmon (especially the DNA, R. Jim, Nov. 2014).…”
Section: Hanford Site As a Case Study: Multiple Ecologicies Stakehold...mentioning
confidence: 73%
“…The tangible outcome of the project, which required over 5 years to complete, was a report to DOE laying out our findings (Burger et al., 2015; CRESP, 2015; Gochfeld & Burger, 2014). The main findings were that: (1) salmon life cycles are varied and complex (involving spring and fall runs, Healey, 1991), (2) having good population estimates by species and runs is critical (Hyun et al., 2012a,b), (3) several species of salmon spend a significant part of their life cycle in the Columbia River (and mainly in the Hanford Reach) where they spawn (Hayes et al., 2013), (4) contaminants are not viewed generally by the State or DOE as a significant stressor on salmon, especially compared to other stressors (CRESP, 2015; NRC, 1996; Regetz, 2003; Tiller et al., 2004), (5) laboratory experiments indicated that there is a great deal of variability in results, no effects were found at Hanford‐relevant chromium exposures on fertilization, hatching, and exposure of alevins (early stage on salmon), but there were some laboratory effects of chromium on later stages of fry (Farag et al., 2006a,b; Patton et al., 2007), and (6) at some periods of time the fry may be vulnerable to chromium if they remain near the gravel surface where the pore water and river water meet (Burger et al., 2015; CRESP, 2015; Gochfeld & Burger, 2014). The Tribes, however, remained concerned about potential long‐term effects of contaminants on eggs and fry of salmon (especially the DNA, R. Jim, Nov. 2014).…”
Section: Hanford Site As a Case Study: Multiple Ecologicies Stakehold...mentioning
confidence: 73%
“…Continuation of past trends of earlier spring peak, more extreme high flows and more frequent low flows in the low elevation basins of northeast Oregon, home to the CTWS and CTUIR, may force earlier migration of juvenile salmon, challenge returning adults in low flow conditions, and increase scour risk for emerging young salmon . One study suggests that monitoring climate change impacts to salmon and their importance for tribal cultural and societal health could be achieved with indicators such as percent of successful tribal fishing trips, ability to obtain sufficient fish for traditional feasts, or percent of streams still with spawning salmon (Burger et al, 2015).…”
Section: Fish Habitat Implicationsmentioning
confidence: 99%
“…The measured concentration reflects the total exposure from all routes (i.e., ingestion, inhalation, and absorption) [12]. Wildlife biomonitoring has long been used to quantify levels of contaminants in the environment and ascribe risk using key sentinel species [12][13][14]. While invasive or destructive samples are used, as is the case for the collection of liver or muscle samples, there have recently been initiatives to move towards non-lethal and non-invasive biomonitoring techniques, including the use of fur [15,16] and feces [17].…”
Section: Introductionmentioning
confidence: 99%